Reflections on Artificial Intelligence – A Hermeneutic Journey - Motamarri, Saradhi (ACIS, 2014)
Science, engineering and technology have been moulding and placing an ever increasing pressure on society and in turn, on life styles. The inquisitive nature of man has led to the amazing development of computer. In just four decades the computer has changed its role from a mere data cruncher to decision aid. A reading of the Artificial Intelligence, 17 (1-3), January, 1991, Special Volume on Foundations of AI, has motivated me to transcribe some of my long persistent feelings in writing. Loose usage and blown up speculations may bring discredit to concepts. Not founded on the characteristic behaviour of computer and its numerical instability, I fear that the same thing has happened to computers and to the associated fields of study. The purpose of this autoethnographic article is to reflect on the lessons learnt from AI and search for a right perspective for research and practice.